Agglomeration and Urban Manufacture Labor Productivity in Indonesia - Yohanes Nurcahyo Agung Wibowo; Toshihiro Kudo (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2019)
Agglomeration, the spatial concentration of industries in a specific location, has been argued to improve productivity since it could provide positive externalities such as knowledge spillover, input sharing, and labor pooling. This paper examines the effect of large and medium manufacturing industry (LMI) agglomeration on labor productivity. Measuring the output and labor density as agglomeration effect by using 2009-2014 panel data from 44 cities and regions across the metropolitan areas of Indonesia, this study shows that in terms of output share, agglomeration positively contributes to labor productivity. On the other hand, in terms of labor density, agglomeration results in a negative impact on productivity. These findings suggest the government should expand industrial clusters in less densely populated areas, especially outside the island of Java, by providing necessary infrastructures such as electricity, ports, and roads, so that this development creates favorable economic conditions for investment and industrial development in such areas.